Solvent-Free and Scalable Procedure to Prepare PYR13TFSI/LiTFSI/PVDF–HFP Thermoplastic Electrolytes with Controlled Phase Separation and Enhanced Li Ion Diffusion - Gregorio, Víctor (Membranes (Basel), 2019)
Solid electrolytes for Li transport have been prepared by melt-compounding in one single step. Electrolytes are composed of polyvinylidene fluoride–hexafluoropropylene (PVDF–HFP) with PYR13TFSI on its own or with varying concentration of LiTFSI. While the extrusion of PVDF–HFP with PYR13TFSI is possible up to relatively high liquid fractions, the compatibility of PVDF–HFP with LiTFSI/PYR13TFSI solutions is much lower. An organo-modified sepiolite with D-α-tocopherol polyethylene glycol 1000 succinate (TPGS-S) can be used to enhance the compatibility of these blends and allows to prepare homogeneous PYR13TFSI/LiTFSI/PVDF–HFP electrolytes with controlled microphase separations by melt-compounding. The structure and morphology of the electrolytes has been studied by FTIR, differential scanning calorimetry (DSC), SEM, and AFM. Their mechanical properties have been studied by classical strain–stress experiments. Finally, ionic conductivity has been studied in the −50 to 90 °C temperature range and in diffusivity at 25 °C by PFG-NMR. These electrolytes prove to have a microphase-separated morphology and ionic conductivity which depends mainly on their composition, and a mechanical behavior typical of common thermoplastic polymers, which makes them very easy to handle. Then, in this solvent-free and scalable fashion, it is possible to prepare electrolytes like those prepared by solvent casting, but in few minutes instead of several hours or days, without solvent evaporation steps, and with ionic conductivities, which are very similar for the same compositions, above 0.1 mS·cm(−1) at 25 °C. In addition, some of the electrolytes have been prepared with high concentration of Li ion, what has allowed the anion exchange Li transport mechanism to contribute significantly to the overall Li diffusivity, making D(Li) become similar and even clearly greater than D(TFSI).